Pengaruh Budaya Perusahaan dan Motivasi Kerja Terhadap Kinerja Karyawan pada PT. Rekayasa Industri - Lina Mardiana; Rony Edward Utama; Roikhan Mochamad Azis (Media Riset Bisnis Ekonomi Sains dan Terapan, 2023)
This study aims to examine and analyze the influence of corporate culture and work motivation on employee performance. The data analysis method used is a quantitative method that is associative by testing the hypothesis. The research source used is primary data. The sampling technique used is a saturated sample, with a total sample tested of 62 respondents who are employees at PT. Industrial Engineering. The data technique is using a questionnaire distributed via Google Form to employees of PT. Industrial Engineering. Data analysis in this study used IBM SPSS Statistics V.23. The results of this study indicate that corporate culture (organization) has a positive and significant effect on employee performance with a t count t table (2.217 2.009) with a significant value of 0.030 less than 0.05 or 5% (0.030 0.05) . Work motivation has a positive and significant effect on employee performance with a t count t table (4.739 2.009) with a significant value of 0.000 less than 0.05 or 5% (0.000 0.05). Corporate culture (organization) and work motivation together (simultaneously) have a positive and significant effect on employee performance with an F count F table (39.871 3.15) with a significant value of 0.000 less than 0.05 or 5% (0.000 0.05).Keywords : Corporate Culture, Work Motivation, Employee perfomance